2014
DOI: 10.1371/journal.pone.0103837
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Germ Cell Genes Expressed in the F9 Testicular Teratoma Stem Cell Line

Abstract: The F9 cell line, which was derived from a mouse testicular teratoma that originated from pluripotent germ cells, has been used as a model for differentiation. However, it is largely unknown whether F9 cells possess the characteristics of male germ cells. In the present study, we investigated spermatogenic stage- and cell type-specific gene expression in F9 cells. Analysis of previous microarray data showed that a large number of stage-regulated germ cell genes are expressed in F9 cells. Specifically, genes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(53 reference statements)
2
12
0
Order By: Relevance
“…We previously reported that GFP-TEX13 can shuttle between the nucleus and cytoplasm in NIH 3T3 and F9 cells [19], and our present immunostaining results confirmed the nuclear localization of TEX13 in vivo (Fig. 2).…”
Section: The Tex13 Protein Localizes To the Nucleus Of Mouse Testiculsupporting
confidence: 90%
See 1 more Smart Citation
“…We previously reported that GFP-TEX13 can shuttle between the nucleus and cytoplasm in NIH 3T3 and F9 cells [19], and our present immunostaining results confirmed the nuclear localization of TEX13 in vivo (Fig. 2).…”
Section: The Tex13 Protein Localizes To the Nucleus Of Mouse Testiculsupporting
confidence: 90%
“…B). This contrasts with the mRNA expression of Tex13 , which reportedly begins at postnatal day 8, corresponding to the appearance of spermatogonia . Because of meiotic sex chromosome inactivation (MSCI), a majority of sex‐linked genes are transcriptionally suppressed from primary meiotic germ cells .…”
Section: Resultsmentioning
confidence: 98%
“…Similar effects were observed in F9 mouse embryonal carcinoma cells, a cell line issued from a mouse testicular teratoma, which shares a number of pluripotency markers with embryonic stem cells as well as gonocytes [ 15 , 16 , 29 , 30 ]. In F9 cells, which express genes from both the somatic and germline lineages, RA treatment can induce the expression of markers of somatic (e.g., collagen IV) and germ cell (e.g., Stra8) fates, depending of the culture conditions and downstream pathway activated [ 16 , 30 ]. All TGCTs, including embryonal carcinoma, are believed to derive from a common precursor, the carcinoma in situ, itself resulting from the failed differentiation of gonocytes [ 18 ].…”
Section: Discussionsupporting
confidence: 54%
“…F9 embryonal carcinoma cells are stem cells of testicular carcinoma, and have the ability to differentiate into three embryonic layers [ 33 ]. Although F9 cells are considered to be similar to embryonic cells, the former can transcribe germ cell-specific genes and possess the characteristics of male germ cells [ 34 ]. Immortalized GC-1 cells exhibit the characteristics of a stage between type B spermatogonia and primary spermatocytes [ 35 ], while GC-2 cells were derived from cells arrested at a premeiotic stage and exhibit the characteristics of spermatocytes [ 36 ].…”
Section: Resultsmentioning
confidence: 99%